Priming and Mining the Civil Engineering Mindset: How Personal Values and Perfectionism Shape Societal Engagement and Consideration in Design - NATHALIE ALKAKOUN (2023)
There are many ongoing calls for the integration of public welfare needs and concerns into engineering curricula and practice; for example, promoting social consciousness, human-centred design, and other socially-related frameworks. However, some engineering students still seem to devalue or resist these initiatives. This project attempts to overcome this problem by exploring a new methodology to facilitate such integrations, whilst bypassing the possible resistance. In the first intervention, this project explores to facilitate such notions via exploiting the psychology-informed approach of priming. Results of the first intervention showed that the priming initially intended to raise empathy (and by extension, social consciousness) scores unexpectedly resulted in significantly decreasing them. This initiated the second and third interventions, which explored how different key facets of the mindset (i.e., personal values and perfectionism, respectively) contribute to decision-making, particularly in contexts of human-centred designing and socially relevant initiatives, in civil engineering design. Such research on exploring the engineering mindset was to also inform the under-explored research literature on the subjective nature of sustainable decision-making in engineering. .. The second and third interventions therefore serve to fill the gap on addressing the subjective nature of sustainable decision-making in engineering, by researching to understand how the different facets of the mindset (i.e., personal values and perfectionism, respectively) dictate decision-making and facilitate (or hinder) social engagement and consideration in human-centric designing and socially considerate contexts. The influence of priming on such decision-making processes and social considerations were also observed in light of the different facets of the mindset. Results show that the majority of civil engineering undergraduates hold dominant Higher Order Values rooted in Self Transcendence (60.87%), and were categorised as perfectionists (74.48%). Findings indicate that those with Higher Order Value rooted in Self Transcendence were significantly less likely to produce what I term Communal Designs (i.e., designs that inform the metaphysical as well as the physical needs of the end-user), compared to those with dominant values rooted in the Higher Order Value of Openness to Change. Students were also found to transition in value towards the Higher Order Value of Conservation with time (i.e., with transition from year 1 to year 3 in a civil engineering programme), and thus transition away from their likelihood of producing Communal Designs by extension. Similarly, those categorised as perfectionists were significantly less likely to produce Communal Designs compared to those categorised as non-perfectionists. Perfectionists were later found to be associated with the Higher Order Value of Conservation when resumed back to the literature for sense-making of the present findings. Underlying common motives of Self-Protection and Anxiety-Avoidance were thus deduced to be hindering ‘truthful’ (i.e., intrinsically driven) engagement with human-centric initiatives, and production of what I termed Communal Designs. An intention-behaviour gap was found prominent in civil engineering undergraduates perhaps intending to, but then failing to produce Communal Designs. Further, the reversed influence of the priming was then discussed to be relative to the underlying motives of self-protection and anxiety-avoidance of the civil engineering undergraduates. Findings of the present project thus serve as a foundation for future mitigative studies or interventions promoting socially considerate initiatives or practices in civil engineering designs.